2002
DOI: 10.1063/1.1512330
|View full text |Cite
|
Sign up to set email alerts
|

Raman characterization of boron-doped multiwalled carbon nanotubes

Abstract: We present first-and second-order Raman spectra of boron-doped multiwalled carbon nanotubes. The Raman intensities are analyzed as a function of the nominal boron concentration. The intensities of both the D mode and the high-energy mode in the first-order spectra increase with increasing boron concentration, if normalized with respect to a second-order mode. We interpret this result as an indication that the high-energy mode in carbon nanotubes is defect-induced in a similar way as the D mode. Based on this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(79 citation statements)
references
References 23 publications
5
74
0
Order By: Relevance
“…In fact, the intensity ratio I D /I G 0 is suggested to be a sensitive measure for the defect concentration in carbon nanotubes by some authors. 57,58 An assignment of additional modes visible in the Raman spectra of SWCNTs can be found in the review articles by Saito et al 59 and Dresselhaus et al…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the intensity ratio I D /I G 0 is suggested to be a sensitive measure for the defect concentration in carbon nanotubes by some authors. 57,58 An assignment of additional modes visible in the Raman spectra of SWCNTs can be found in the review articles by Saito et al 59 and Dresselhaus et al…”
Section: 21mentioning
confidence: 99%
“…The influence of defect densities on the relative Raman intensities has also been studied in multiwalled carbon nanotubes. 57,92 Here, no further increase 57 Figure 3. D-and G-band intensity at exc D 532 nm with respect to degree of functionalization using diazonium reagents.…”
Section: D-band Intensity As a Measure Of Functionalization Vsdefect mentioning
confidence: 99%
“…Raman spectra of the silica fibres before and after MWCNT grafting are shown in Several studies [41][42][43] have reported that normalising the D mode intensity with respect to the intensity of the G ' mode is a more reliable method for estimating the defect concentration in nanotube samples [42]. A comparison of the various possible ratios of the Raman signals as a function of position, calculated based on both peak intensity ( Figure 5e) and area (Figure 5f) showed similar trends in all cases.…”
Section: Raman Characterisationmentioning
confidence: 99%
“…[17] The intensity of the D-line is related to the amount of sp 3 defects within the nanotubes, which lower the crystal symmetry of the sp 2 material. [18] Therefore, we concentrate on the changes in the D-line intensities brought about by ECM. The absolute intensity of the D-line in the Raman spectra cannot be used di- After ECM and topological characterization by AFM, the confocal Raman imaging was repeated and the spectra were taken at the same locations as before.…”
mentioning
confidence: 99%